Upaya Peningkatan Maharah Kalam Melalui Kegiatan Intrakurikuler Muhadharah - Mutia Insani; Wagino Hamid Hamdani; Asep Sopian (An Nabighoh Jurnal Pendidikan Dan Pembelajaran Bahasa Arab, 2021)
The problematics of PPM Al-Jumhuriyah students' language activities are Arabic students of PPM Al-Jumhuriyah are still low, and intracurricular muhadharah activities can support and improve the quality of Arabic students are still lacking. From this, the researcher considers that applying Muhadharah activities plays an essential role in improving the quality of students' Arabic speaking skills. This research was descriptive. It was analyze using qualitative methods. To collect the data, the researcher used interviews, questionnaires, and study documentation. The result is that the management of the process of implementing Muhadharah activities does not yet support the improvement of the quality of students' Arabic speaking skills. Based on the research results on applying Muhadharah activities in improving Arabic speaking skills, it shows several deficiencies and obstacles experienced by students. So the researcher's suggestion for the language mobilizer as a core part of linguistic activities is to vary the method of implementing Muhadharah activities that bring students to ease and encourage students to be more active in speaking languages and advising matters relating to language that runs in the boarding and guarding them.